COMPARATIVE EVALUATION OF HYPERBARIC BUPIVACAINE AND LEVOBUPIVACAINE AS SPINAL ANESTHESIA AGENTS IN FEMALES UNDERGOING CESAREAN SECTION: A CLINICAL PROSPECTIVE STUDY. - Panda, Jagannath; Nayak, Ratikanta; Behera, Susanta Kumar (Student’s Journal of Health Research Africa, 2023)
Background: Due to the anesthetic substance used, obstetric anesthesia treatments must achieve the right level of muscular relaxation and analgesia while minimizing any adverse effects on the mother or fetus. In the current study, levobupivacaine and hyperbaric bupivacaine were compared as spinal anesthetic agents for patients undergoing Lower Segment Cesarean Sections (LSCS). Materials and methods: 120 pregnant women who were scheduled for elective cesarean procedures and belonged to the American Society of Anesthesiologists (ASA) I-II groups participated in the research study. The patients were divided into two groups at random. The combinations of 10 mg levobupivacaine (0.5%) + 15 cg fentanyl for Group L patients (n = 60) and 10 mg hyperbaric bupivacaine (0.5%) + 15 cg fentanyl for Group B patients (n = 60) required 2.3 cc to administer. Results: The maximal dermatome for the sensory block, a two-dermatome regression, and a regression to the T12 dermatome all took a lot longer for Group B than for Group A. It was demonstrated that Group B’s motor block evolution advanced faster and persisted longer. Group L saw fewer instances of hypotension, bradycardia, and nausea, but Group B needed more ephedrine (p ≤ 0.05). Hyperbaric bupivacaine was more frequently associated with hypotension and bradycardia, which affected 66% and 33% of the patients. Conclusion: Levobupivacaine and hyperbaric bupivacaine both quickly and effectively induce surgical anesthetic for elective C-section procedures without having any negative effects on newborns, we would like to state as a conclusion to our study. Levobupivacaine and fentanyl together, however, offer a shorter motor block period, and lower risk of side effects so they should therefore be the preferable choice for elective C-sections. Recommendation: Isobaric levobupivacaine 0.5% can be a good alternative for hyperbaric bupivacaine 0.5% for elective caesarean sections.